Improving the rheometry of rubberized bitumen: experimental and computation fluid dynamics studies - Lo Presti, Davide; Giancontieri, G.; Hargreaves, David (Elsevier, 2017)
Multi-phase materials are common in several fields of engineering and rheological measurements are intensively adopted for their development and quality control. Unfortunately, due to the complexity of these materials, accurate measurements can be challenging. This is the case of bitumen-rubber blends used in civil engineering as binders for several applications such as asphalt concrete for road pavements but recently also for roofing membranes. These materials can be considered as heterogeneous blends of fluid and particles with different densities. Due to this nature the two components tends to separate and this phenomenon can be enhanced with inappropriate design and mixing. This is the reason behind the need of efficient dispersion and distribution during their manufacturing and it also explains while realtime viscosity measurements could provide misleading results. To overcome this problem, in a previous research effort, a Dual Helical Impeller (DHI) for a Brookfield viscometer was specifically designed, calibrated and manufactured. The DHI showed to provide a more stable trend of measurements and these were identified as being ‘‘more realistic” when compared with those obtained with standard concentric cylinder testing geometries, over a wide range of viscosities. However, a fundamental understanding of the reasons behind this improvement is lacking and this paper aims at filling these gaps. Hence, in this study a tailored experimental programme resembling the bitumen-rubber system together with a bespoke Computational Fluid Dynamics (CFD) model are used to provide insights into DHI applicability to perform viscosity measurements with multiphase fluids as well as to validate its empirical calibration procedure. A qualitative comparison between the laboratory results and CFD simulations proved encouraging and this was enhanced with quantitative estimations of the mixing efficiency of both systems. The results proved that CFD model is capable of simulating these systems and the obtained simulations gave insights into the flow fields created by the DHI. It is now clear that DHI uses its inner screw to create a vertical dragging of particles within a fluid of lower density, while the outer screw transports the suspended particles down. This induced flow helps keeping the test sample less heterogeneous and this in turns allows recording more stable viscosity measurements.